Clinical and immunological characteristics of high-risk double-hit multiple myeloma - Shang, Yufeng; Chen, Guopeng; Liu, Li; Pan, Ruiyang; Li, Xinqi; Shen, Hui; Tan, Yuxin; Ma, Linlu; Tong, Xiqin; Wang, Weida; Chen, Xiaoqin; Xia, Zhongjun; et al. (BMC cancer, 2024)
At present, the characteristics of double-hit multiple myeloma (DHMM) are unknown. We retrospectively analyzed the clinical data from 433 new diagnosed MM patients and found that DHMM have a higher β2-MG level and percentage of bone marrow plasma cell. Cox regression analysis showed that the prognosis of DHMM was not limited by clinical indicators. The abnormal proliferation of bone marrow in DHMM is obvious, and the proportion of poorly differentiated plasma cell is high. By collecting specimens from our center and performing flow cytometry to analyze the immunophenotypic and functional characteristics of lymphocyte subpopulations, we found that DHMM had a higher ratio of Tregs cells, and the proportion of iTregs cells was also significantly higher than non-DHMM (P < 0.05). Moreover, DHMM had higher levels of TGF-β1 and IL-10, and TGF-β1 and IL-10 were positively correlated with iTregs (P < 0.05). In addition, DHMM was highly expressed PD-1 on CD8 + T cells and had a higher proportion of CD38 Tregs cells. In vitro we have shown that the addition of TGF-β1 antibody or CD38 antibody can effectively inhibit the proportion of CD38 Tregs. This study describes the characteristics of DHMM based on bicentric data, which is helpful to better provide theoretical support for the treatment of DHMM.